Positive short term effects of an integrative korean medicine treatment package for low back pain caused by motor vehicle accidents: A retrospective chart review of real – world practice data - Park, Hye-Rin; Lee, Seungmin Kathy; Yoon, Sang-Hoon; Jo, Hee-Geun; Kim, Ji-Yong; Kim, Hyunho; Sul, Jae-Uk; Leem, Jungtae (Frontiers in Pharmacology, 2022)
Backgrounds No standard treatment exist for reducing symptoms related to sequelae of motor vehicle accidents (MVAs). In Korea, comprehensive Korean Medicine (KM) treatment that includes botanical drugs (herbal medicine), acupuncture, pharmacopuncture, tuina, moxibustion, and cupping is covered by automobile insurance and increasingly used to help alleviate such pain. This study aimed to analyze real-world data and to evaluate the effectiveness and safety of comprehensive KM treatment for low back pain caused by MVAs. Methods We conducted a retrospective chart review of patients who received KM treatment during hospitalization. Records that lacked follow-up outcome assessments were excluded. The Verbal Numerical Rating Scale (VNRS), the Korean version of the Oswestry Disability Index (K-ODI) and the Korean version of the Roland-Morris Disability Questionnaire (K-RMDQ) were evaluated at admission and discharge. Adverse events were also analyzed. A paired t-test was used to identify the effectiveness of KM treatment. Results A total of 50 patients, 30 males and 20 females, were included in the analysis. The mean age of the patients was 40.72 ± 13.31 years and the average treatment period was 7.22 ± 3.84 days. After treatment, VNRS, K-ODI and K-RMDQ were significantly improved (p < 0.001). There was a decrease from 5.06 ± 1.60 to 3.40 ± 1.81 in VNRS, 33.38 ± 16.88 to 24.54 ± 13.63 in K-ODI, and 6.84 ± 6.27 to 4.14 ± 4.38 in K-RMDQ. During this period, a total of two adverse events were reported. Discussion Although this retrospective chart review looked into the short term effects only, comprehensive KM treatment might be an effective and safe therapeutic option to reduce acute low back pain especially after MVA. Prospective research data is needed to support this hypothesis.